2023
DOI: 10.1111/cpr.13444
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin‐specific peptidases: Players in bone metabolism

Abstract: Osteoporosis is an ageing‐related disease, that has become a major public health problem and its pathogenesis has not yet been fully elucidated. Substantial evidence suggests a strong link between overall age‐related disease progression and epigenetic modifications throughout the life cycle. As an important epigenetic modification, ubiquitination is extensively involved in various physiological processes, and its role in bone metabolism has attracted increasing attention. Ubiquitination can be reversed by deub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 153 publications
0
3
0
Order By: Relevance
“…The SNP_ 25:38,081,982 is near the genes USP42 and ANKRD61. The USP family plays an empirical role in posttranslational modification and protein homeostasis by regulating cellular activity [ 75 ]. USP proteins are involved in aspects of bone growth as identified in humans and mice [ 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNP_ 25:38,081,982 is near the genes USP42 and ANKRD61. The USP family plays an empirical role in posttranslational modification and protein homeostasis by regulating cellular activity [ 75 ]. USP proteins are involved in aspects of bone growth as identified in humans and mice [ 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both genes influence or regulate ubiquitylation. Ubiquitin is a regulatory protein important in cell signaling [ 75 , 76 ], including bone cells, as ubiquitin-dependent endocytosis is required to remove the receptors on the surface. This includes receptors that bind bone morphogenic proteins (BMP).…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin‐specific peptidases (USPs) are major members of the deubiquitinating enzyme family (Shen et al., 2023; Young et al., 2019), and are capable of recognizing the ubiquitination signals of specific proteins to deubiquitinate the target proteins (Fu et al., 2023). Previous study found that USP47 promoted osteogenic transdifferentiation to mediate vascular calcification in chronic kidney disease (Xiao et al., 2022).…”
Section: Introductionmentioning
confidence: 99%